The impact of India's demonetization on domestic agricultural trade - Aggarwal, Nidhi; Narayanan, Sudha (Wiley, 2023)
We examine the impact of an extreme monetary shock, India's demonetization of 2016, on domestic agricultural trade. Using data from around 3000 regulated markets for 35 major crops, we find that trade value fell by 16.3–16.8% in the short run, settling at 11.8–12.1% after eight months, driven primarily by a decline in prices. Triple difference estimates suggest sharpest impacts for kharif crops, perishables and crops with minimal government intervention. Markets far away from banks fared worse. Our results suggest that the implosion of value of agricultural trade domestically persisted two growing seasons beyond the one that coincided with the shock, whereas existing findings suggest that the negative impact on the economy as a whole dissipates in that time.